Close Range Photogrammetry - Principles, techniques and applications - Luhmann, Thomas (Whittles Publishing, 2011)
This book provides a thorough presentation of the methods, mathematics, systems and applications which comprise the subject of close range photogrammetry, which uses accurate imaging techniques to analyse the three-dimensional shape of a wide range of manufactured and natural objects. After an introduction, the book provides fundamental mathematics, including orientation, digital imaging processing and 3-D reconstruction methods, as well as presenting a discussion of imaging technology including targeting and illumination, hardware and software systems.